Reality bytes : cyberterrorism and terrorist use of the Internet - Conway, Maura (Trinity College (Dublin, Ireland). Department of Political Science, 2006)
The analysis contained herein treats the relationship between terrorism and the internet. Instead of treating cyberterrorism as the most important conjunction of terrorism and the Internet (as has been the tendency to date - even amongst those who doubt the efficacy of the cyberterrorist threat), this study illustrates how terrorist use of the Net is an everyday 'reality' and one that ought to attract far more attention than it has yet received. The study places a particular emphasis on terrorist Web sites as the vehicles for terrorist publicity and propaganda, one of the most prominent contemporary terrorist uses of the Net. but also seeks to balance claims about the power of 'small media,' such as the Internet, against the continued dominance of the traditional mass media (i.e. 'big media').
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin